PARASITES THAT POSE A THREAT TO THE HUMAN BODY AND MODERN BIOPHYSICALLY BASED SOLUTIONS AGAINST THEM (The New Uzbekistan Journal of Medicine, 2025)
The article discusses the helminths that are dangerous for the human body - nematodes (roundworms) worms), trematodes (flukes) and cestodes (tapeworms) classes and their main parasitic species, their disease-causing properties and measures to combat them are covered.